A Cretaceous carbonate delta drift in the Montagna della Maiella, Italy. Issue 4 (29th April 2019) - Eberli, Gregor P.; Bernoulli, Daniel; Vecsei, Adam; Sekti, Rizky; Grasmueck, Mark; Lüdmann, Thomas; Anselmetti, Flavio S.; Mutti, Maria; Porta, Giovanna Della
Abstract: The Upper Cretaceous (Campanian–Maastrichtian) bioclastic wedge of the Orfento Formation in the Montagna della Maiella, Italy, is compared to newly discovered contourite drifts in the Maldives. Like the drift deposits in the Maldives, the Orfento Formation fills a channel and builds a Miocene delta‐shaped and mounded sedimentary body in the basin that is similar in size to the approximately 350 km 2 large coarse‐grained bioclastic Miocene delta drifts in the Maldives. The composition of the bioclastic wedge of the Orfento Formation is also exclusively bioclastic debris sourced from the shallow‐water areas and reworked clasts of the Orfento Formation itself. In the near mud‐free succession, age‐diagnostic fossils are sparse. The depositional textures vary from wackestone to float‐rudstone and breccia/conglomerates, but rocks with grainstone and rudstone textures are the most common facies. In the channel, lensoid convex‐upward breccias, cross‐cutting channelized beds and thick grainstone lobes with abundant scours indicate alternating erosion and deposition from a high‐energy current. In the basin, the mounded sedimentary body contains lobes with a divergent progradational geometry. The lobes are built by decametre thick composite megabeds consisting of sigmoidal clinoforms that typically have a channelized topset, a grainy foreset and a fine‐grained bottomset with abundant irregular angular clasts. Up to 30 m thick channels filled with intraformational breccias and coarse grainstones pinch out downslope between the megabeds. In the distal portion of the wedge, stacked grainstone beds with foresets and reworked intraclasts document continuous sediment reworking and migration. The bioclastic wedge of the Orfento Formation has been variously interpreted as a succession of sea‐level controlled slope deposits, a shoaling shoreface complex, or a carbonate tidal delta. Current‐controlled delta drifts in the Maldives, however, offer a new interpretation because of their similarity in architecture and composition. These similarities include: (i) a feeder channel opening into the basin; (ii) an excavation moat at the exit of the channel; (iii) an overall mounded geometry with an apex that is in shallower water depth than the source channel; (iv) progradation of stacked lobes; (v) channels that pinch out in a basinward direction; and (vi) smaller channelized intervals that are arranged in a radial pattern. As a result, the Upper Cretaceous (Campanian–Maastrichtian) bioclastic wedge of the Orfento Formation in the Montagna della Maiella, Italy, is here interpreted as a carbonate delta drift.